Study on initial fracture distribution and bearing damage evolution mechanism of disturbed coal samples in oil-rich coal deposits in western China - Shao, Yawu; Zhu, Lei; Xin, Chang; Han, Gang; Lin, Haifei; Liu, Hu; Xie, Jiahao; Sun, Mingming; Wang, Jin (Frontiers in Materials, 2026)
The simultaneous formation of stress transfer and structural optimization in deep underground engineering strongly influences the occurrence and severity of dynamic disasters, especially under complex stress–structure conditions. In western China, oil-rich coal is mainly distributed in complex geological structures, and the deformation, fracture, and failure of coal are essentially governed by fracture evolution under external loading. Therefore, the characteristics of the original fissure structure and the subsequent damage evolution process are critical for multi-source disaster prevention and control during oil-rich coal mining. In this study, the initiation, propagation, coalescence, and evolution of coal microfissures under multi-stage disturbances were investigated using CT scanning combined with mechanical testing. Differences in CT images among different regions were analyzed after initial oil and gas resource exploitation, and crack binary images were used to qualitatively describe fracture evolution. Meanwhile, coal CT number, crack number, trace width, gap length, and crack density were extracted to quantitatively characterize the spatio-temporal relationship between fracture structural features and multi-stage repeated disturbances, together with acoustic emission characteristics. The results provide a comprehensive description of fracture development and damage progression in disturbed coal samples, which is of great significance for understanding the fracture distribution and mechanical response mechanisms, thereby supporting safe and efficient coordinated mining of oil-rich coal in western China.